Orchids diversity of Situ Gunung, Sukabumi - NINA RATNA DJUITA; SRI SUDARMIYATI; HENDRIUS CANDRA; SARIFAH SARIFAH; SITI NURLAILI; RULLY FATHONY (Society for Indonesian Biodiversity, 2004)
Study on the orchids diversity was conducted in Situ Gunung, sub district of Kadudampit, district of Sukabumi, West Java. There were 41 collection numbers, consist of 18 terrestrial orchids, 22 epiphyte orchids, and one saprophyte orchid, belong to 26 genera and 41 species. There were eight species of flowering orchids and the rest were not at flowering stage. Agrostophyllum bicuspidatum J.J.Sm, Plocoglottis acuminata Bl dan Appendicula sp. were commonly found at Situ Gunung. Species orchid of Calanthe triplicata (Willemet) Ames and Plocoglottis acuminata Bl found in a clumped group. Tainia elongata J.J. Sm was the only endemic orchid in Java from this situ.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: orchids, Situ Gunung, Sukabumi.